Compactação e lâminas de água do solo para a colheita de tapetes de grama - Carribeiro, Lívia Sancinetti [UNESP] (2014)
Understanding of the concepts of soil compaction and its relationship to the harvest system of turfgrass sods are important tools to help to establish the appropriate management of soil physical conditions of Zoysiagrass sod production as well as improving its production process. Moreover, following the requirements for soil compaction levels at the moment of the turfgrass sods harvest is the best way to guarantee the quality of turfgrass for the following harvest cycles. In addition to that, it is essential to manage the appropriate levels of water and soil compaction at the moment of harvest. In this sense, the aim of this study was to evaluate the effects of irrigation and soil compaction levels according to the application of different loading levels applied to the soil (using a compactor roller at the moment of the sods harvest), enabling the removal of intact turfgrass sods as well as providing the minimum soil compaction level right below the sod layer removed, so that the subsequent development of turfgrass occurs quickly and appropriately. The experiment was conducted at “Sítio Paraíso” turfgrass commercial farm located in Tatuí – SP, owned by Gramas Xavier Company. It was considered the mechanical system harvest. The evaluation of the results occurred between May 9th, 2012 and May 15th, 2013. The soil in the area was previously characterized as a clay texture soil. It was utilized the turfgrass species Zoysia japonica Steud., commonly known as Esmeralda grass. Plots were arranged in a split-plot experimental design with four replications, with 48 experimental units in total. There were considered two factors of variation: water and compaction intensity. The factor water level (variations between 7.5 , 10 , 12.5 , and 15mm) was established in the day before the establishment of the soil compaction; the factor ...